2020
DOI: 10.1002/ldr.3690
|View full text |Cite
|
Sign up to set email alerts
|

Effects of vegetation restoration on soil nutrients, plant diversity, and its spatiotemporal heterogeneity in a desert–oasis ecotone

Abstract: Vegetation restoration has been proposed as an effective measure for rehabilitating degraded land and slowing desertification in arid regions. However, the spatial variation in soil quality and plant diversity following vegetation restoration remains unclear. This study was designed to explore soil nutrient dynamics and how soil nutrients affect plant diversity and spatial heterogeneity after shrub restoration. We assessed the effect of Haloxylon ammodendron (C.A.Mey.) Bunge (which has been planted over 30 yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 71 publications
1
19
0
Order By: Relevance
“…In addition, different scholars evaluated the ecological restoration effect of CTSRB from the perspectives of groundwater level (Hao et al, 2017), vegetation coverage (Youhao et al, 2007), desertification (Sun et al, 2006), and vegetation diversity (Wu et al, 2021), and proved that CTSRB played a positive role in the restoration of the Minqin ecological environment. This study took a different approach and interpreted the ecological restoration effect of the CTSRB from the perspective of SM.…”
Section: Ecological Effects Evaluation Of the Ctsrb From The Perspect...mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, different scholars evaluated the ecological restoration effect of CTSRB from the perspectives of groundwater level (Hao et al, 2017), vegetation coverage (Youhao et al, 2007), desertification (Sun et al, 2006), and vegetation diversity (Wu et al, 2021), and proved that CTSRB played a positive role in the restoration of the Minqin ecological environment. This study took a different approach and interpreted the ecological restoration effect of the CTSRB from the perspective of SM.…”
Section: Ecological Effects Evaluation Of the Ctsrb From The Perspect...mentioning
confidence: 99%
“…In our study, the SM of the 0.00-0.20 m soil layer showed a downward trend during pre-CTSRB, and the SM decline was greater in the 0.00-0.10 m layer than the 0.10-0.20 m layer. Studies have shown that the groundwater level (Hao et al, 2017) and vegetation (Wu et al, 2021) of the Minqin area during the CTSRB period was more recovered than the pre-CTSRB period. During CTSRB, compared with pre-CTSRB, SM of 0.00-0.10 m gradually decreased while the soil layer of 0.10-0.20 m gradually increased.…”
Section: Relationship Between Sm Changes Groundwater Level and Vegeta...mentioning
confidence: 99%
“…J. Wang et al, 2009), topography (X. S. Gao et al, 2019;Gou et al, 2015;H. J. Wang et al, 2009;Yang et al, 2013), vegetation or biotic condition (Erickson et al, 2005;Li et al, 2007;Wu et al, 2020), socioeconomic factors (Karna & Bauer, 2020;Sklenicka et al, 2020), and human behaviour (land-use type and land management activities) (Gou et al, 2015;H. J. Wang et al, 2009;Yang et al, 2013).…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…Soil fertility is influenced by the natural environment (X. S. Gao et al, 2019;Wu et al, 2020) and socioeconomic and institutional factors, such as extension visits, government support, and cooperative membership (Boardman et al, 2003;Karna & Bauer, 2020;Sklenicka et al, 2020). However, the socioeconomic and institutional factors are not well understood in the literature.…”
mentioning
confidence: 99%
“…International commitment also promotes afforestation through the Bonn Challenge, as 47 countries pledged to having 350 million hectares of degraded and deforested lands (hereafter degraded lands) under revegetation or reforestation by 2030 (Verdone & Seidl, 2017). Previous studies demonstrated that land transformation from degraded land to tree plantations has significantly improved aboveground vegetation cover, carbon sequestration, and soil properties (Wu et al, 2021). In this context, forest management practices play a decisive role in the successful establishment of trees on degraded land (Burnett et al, 2019; Filyushkina et al, 2018).…”
Section: Introductionmentioning
confidence: 99%